Community College Program Choices in the Wake of Local Job Losses - Acton, Riley K. (Journal of Labor Economics, 2021)
Deciding which field to study is one of the most consequential decisions college students make, but most research on the topic focuses on students attending four-year colleges. To understand how students attending community colleges make field of study decisions, the author links administrative educational records of recent high school graduates with local mass layoff and plant closing announcements. He finds that declines in local employment deter students from entering closely related community college programs and instead induce them to enroll in other vocationally-oriented programs. He further documents that students predominantly shift enrollment between programs that lead to occupations requiring similar skills.